How to sensitize glioblastomas to temozolomide chemotherapy: a gap-centered view - Miramova, Alila; Gartner, Anton; Ivanov, Dmitri (Frontiers in Cell and Developmental Biology, 2024)
Temozolomide (TMZ) is a methylating agent used as the first-line drug in the chemotherapy of glioblastomas. However, cancer cells eventually acquire resistance, necessitating the development of TMZ-potentiating therapy agents. TMZ induces several DNA base adducts, including O6 -meG, 3-meA, and 7-meG. TMZ cytotoxicity stems from the ability of these adducts to directly (3-meA) or indirectly (O6 -meG) impair DNA replication. Although TMZ toxicity is generally attributed to O6 -meG, other alkylated bases can be similarly important depending on the status of various DNA repair pathways of the treated cells. In this mini-review we emphasize the necessity to distinguish TMZ-sensitive glioblastomas, which do not express methylguanine-DNA methyltransferase (MGMT) and are killed by the futile cycle of mismatch repair (MMR) of the O6 -meG/T pairs, vs TMZ-resistant MGMT-positive or MMR-negative glioblastomas, which are selected in the course of the treatment and are killed only at higher TMZ doses by the replication-blocking 3-meA. These two types of cells can be TMZ-sensitized by inhibiting different DNA repair pathways. However, in both cases, the toxic intermediates appear to be ssDNA gaps, a vulnerability also seen in BRCA-deficient cancers. PARP inhibitors (PARPi), which were initially developed to treat BRCA1/2-deficient cancers by synthetic lethality, were re-purposed in clinical trials to potentiate the effects of TMZ. We discuss how the recent advances in our understanding of the genetic determinants of TMZ toxicity might lead to new approaches for the treatment of glioblastomas by inhibiting PARP1 and other enzymes involved in the repair of alkylation damage (e.g., APE1).